2022
DOI: 10.7759/cureus.21108
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Comparison of the Heart and Left Anterior Descending Artery in Patients With Left Breast Cancer Treated With Three-Dimensional Conformal and Intensity-Modulated Radiotherapy

Abstract: Background Adjuvant radiotherapy plays an important role in the management of breast cancer, along with surgery and chemotherapy. However, postoperative radiotherapy poses an increased risk of radiation-induced heart diseases in patients with left-sided breast cancer due to damage of the coronary arteries, which can cause myocardial fibrosis and coronary artery disease; however, there is a lack of sufficient evidence for it. Hence, the present study aimed to assess the dosimetric parameters of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Several dosimetric studies have investigated the dosimetric implications of breast radiation on cardiac risk, especially for left-sided tumor and internal mammary chain radiation [10,11]. A study done by Garg and Kumar has shown that V 25 to the heart with 3D-CRT was 14.13 and IMRT 27.74 Gy [12]. In a dosimetric study comparing post-mastectomy IMRT and 3D-CRT, Khullar et al showed that except for the mean dose to the opposite breast, the compliance to DVH constraints for PTV and OARs was significantly improved with IMRT [13].…”
Section: Discussionmentioning
confidence: 99%
“…Several dosimetric studies have investigated the dosimetric implications of breast radiation on cardiac risk, especially for left-sided tumor and internal mammary chain radiation [10,11]. A study done by Garg and Kumar has shown that V 25 to the heart with 3D-CRT was 14.13 and IMRT 27.74 Gy [12]. In a dosimetric study comparing post-mastectomy IMRT and 3D-CRT, Khullar et al showed that except for the mean dose to the opposite breast, the compliance to DVH constraints for PTV and OARs was significantly improved with IMRT [13].…”
Section: Discussionmentioning
confidence: 99%